2020
DOI: 10.15561/26649837.2020.0605
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-season football training on hematological parameters of well-trained young male football players

Abstract: Background and Study Aim. The purpose of this study was to examine the effect of metabolic stress created by 6-week football training applied in the pre-season period on circulation and hematological parameters of well-trained male football players.  Material and Methods. Fourteen male football players who competed in the U19 category of a football team in Turkish Football Super League participated in the study voluntarily. In the study, players’ systolic - diastolic blood pressures and resting h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…Moreover, a study conducted on 13 male soccer players, with significant augment in PLT levels (209.76 ± 33.83 to 249.76 ± 61.09 × 103/µL) was noted following 2 weeks of pre-tournament moderate-to-high intensity training period [ 49 ]. Contrary to our study, Ozen et al [ 50 ] found an increase in PLT after the pre-season training period in well-trained young soccer players. However, their reported increase (pre: 205.57 ± 54.94, post: 214.85 ± 23.12) was not significant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study conducted on 13 male soccer players, with significant augment in PLT levels (209.76 ± 33.83 to 249.76 ± 61.09 × 103/µL) was noted following 2 weeks of pre-tournament moderate-to-high intensity training period [ 49 ]. Contrary to our study, Ozen et al [ 50 ] found an increase in PLT after the pre-season training period in well-trained young soccer players. However, their reported increase (pre: 205.57 ± 54.94, post: 214.85 ± 23.12) was not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…In other study, it was noted that there was an increase in neutrophils and a decrease in lymphocytes after short periods of pre-tournament training [ 49 ]. Ozen et al [ 50 ] reported no significant differences in subpopulations of leukocytes (lymphocytes, neutrophil, monocyte, and basophil percentage) after the pre-season period in young male football players. In a previous study, which was not consistent with the findings of our study in terms of neutrophil, an increase in neutrophil counts was found after regular and vigorous soccer exercises, and it was suggested that this situation was associated with minor inflammatory events [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…N I represents the torque contribution of each muscle at different training stages. 6 We use Equation ( 4) to extract the biomechanical features of the muscles under different training stages…”
Section: Muscle Biomechanical Effects Of Football Playersmentioning
confidence: 99%
“…11 Hematological parameters are affected by both the frequency, intensity, type and duration of the exercise, as well as the age of the person, eating habits and the environment. 12 In many studies, it has been shown that regular training makes changes the hematological patterns of many athletes, including TKD, but in some studies it does not. [13][14][15][16] Due to the close contact between the athletes during the TKD sport, the risk of injury that causes various levels of tissue damage has always been inherent in this sport.…”
Section: Introductionmentioning
confidence: 99%